2019
DOI: 10.1037/hea0000697
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of NIH PROMIS® instruments in bariatric surgery candidates.

Abstract: Objective: Ascertain the psychometric properties of the Patient-Reported Outcomes Measurement Information System® (PROMIS®) Depression (PROMIS-D®) and Anxiety (PROMIS-A®) Short Forms in a sample of presurgical bariatric patients. Method: This retrospective chart review included 259 patients who completed a presurgical psychological evaluation comprising a semistructured interview and self-report measures. Other data used included demographics, psychiatric diagnoses, and initial psychological clearance for surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…-The National Institute of Health (NIH) Patient-Reported Outcomes Measurement Information System (PROMIS) Anxiety SF [27] is a 7-item self-report questionnaire assessing symptoms of anxiety. The NIH PROMIS Anxiety SF has been previously administered among a sample of bariatric patients and has been found to have good psychometric properties [28]. [27] consists of 8 items that assess symptoms of depression.…”
Section: Nih Promis Anxiety Short Form (Sf)mentioning
confidence: 99%
See 3 more Smart Citations
“…-The National Institute of Health (NIH) Patient-Reported Outcomes Measurement Information System (PROMIS) Anxiety SF [27] is a 7-item self-report questionnaire assessing symptoms of anxiety. The NIH PROMIS Anxiety SF has been previously administered among a sample of bariatric patients and has been found to have good psychometric properties [28]. [27] consists of 8 items that assess symptoms of depression.…”
Section: Nih Promis Anxiety Short Form (Sf)mentioning
confidence: 99%
“…[27] consists of 8 items that assess symptoms of depression. Previous research has administered the NIH PROMIS Depression SF to a sample of bariatric patients and found the measure to be reliable and valid [28]. [29] is a 21-item measure of anxiety symptoms in the past week with scores ranging from 0 (not at all) to 3 (severely).…”
Section: Nih Promis Anxiety Short Form (Sf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Extending the range of clinical samples in which PROMIS measures have been investigated, Kudel and colleagues (Kudel et al, 2019) studied the psychometric properties of selected PROMIS instruments in bariatric surgery candidates. They administered PROMIS Depression and Anxiety short forms to presurgical bariatric patients and found that both measures demonstrated good reliability, validity, and measurement invariance across race and sex.…”
Section: Extending Promis Validitymentioning
confidence: 99%